Socio-economic impacts of Parthenium hysterophorus L. in East Shewa and West Arsi zones of Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2017)
Parthenium hysterophorus L. is non-native invasive plant species belongs to the family Asteraceae. Currently it is a notorious weed in Ethiopia. Socio-economic impacts as well as the local peoples perception towards P. hysterophorus are poorly understood. Thus, the aim of this study was to generate information for a better understanding of the means of dispersal, source introduction and socio-economic impacts, of P. hysterophorus in East shewa and West arsi Zones of the Oromia Regional State of Ethiopia. The study revealed that parthenium was introduced mainly by following vehicles road and railways. This weed grows throughout the year. This results in its fast dispersal. Many mechanisms were assumed by respondents for fast distribution of P. hysterophorus in the study zones. Among these vehicles and wind are the major agents, which proliferate the seeds of the weed. Based on the study it grows in roadsides, grazing land, cropland, village sides and wastelands. Most of respondents also indicated that the weed first appeared on roadside and propagated to other habitats. This finding indicated that the weed high in disturbed habitats. Control methods, which are mostly practiced by local people, were tillage and hand weeding. However, these methods were not an efficient to control the weed distribution; rather it is expanding from time to time since its invasions. P. hysterophorus has a number of socioeconomic impacts that include effect on crop and livestock production, human health, soil fertility and biodiversity. This finding showed that it competes and suppress the growth of crops due its allelopathic nature. Seeds of this weed changes the normal flavor of food when mix with it. It also colonized grazing fields, thus causing animal food scarcity, animals health defect. This finding also reported that P. hysterophorus has health hazards on human being, which include allergic, skin itching (irritation), cough and hemorrhage. Generally, P. hysterophorus is a foremost troublesome weed and subterfuge threat on agriculture, biodiversity and on human health. Therefore, proper and targeted control methods should be employed to control the further spread and reduce the adverse impacts.Int. J. Agril. Res. Innov. & Tech. 6 (2): 5-11, December, 2016